Variation in Nepali Verb Roots: A Phonological Perspective - Regmi, Bhim Narayan (Gipan, 2025)
This study explores the explanability of the variation in Nepali verb roots from phonological perspective and the availability of clues of phonological processes in the written form. The data for this study are phonemically transcribed 1892 verb roots containing 3312 syllables selected from Prajñā Nepālī Bṛhat Śabdakośa. (2079BS). Among these 933 verb roots with variations are classified into syllable based variations that contains four types and segment based variations that contains ten types. CV is the most frequent syllable structure in Nepali followed by CVC. Nepali belongs to the group of languages with moderately complex syllable structure. The study finds that there are clues of phonological process in the written form, and explains the variations in the verb roots in terms of phonemic environment, syllable structure and syllable weight. Though not allowed in the surface, super heavy syllables are at the abstract underlying level in Nepali verb roots. Almost all the syllable based variations are resulted in course of the simplification of the super heavy syllable to make the structure permissible.